« Une clé confectionnée sans la moindre idée de la serrure où un jour elle pourrait être introduite » : Les Fleurs du mal chez Walter Benjamin - Yoann Loir (Association Portugaise d'Etudes Françaises, 2021)
Formulating a book project on Baudelaire, Walter Benjamin set himself the task of making the poet's imprint on the nineteenth century appear as clearly as that of “a stone that one day is rolled away from the spot on which it has rested for decades”. We will show that it was less a question of showing the anchoring of the work in its century than of extracting it from its historical context in order to draw out possibilities. The philosopher conceived The Flowers of Evil as a "key made without the slightest idea of the lock into which it might one day be inserted", as a condition for access to knowledge of the 20th century. We will retrace the appropriation of the lyric work from the young translator's reflections to the moment when his mature work converges with it and rewrites its motifs. We will finally bring out how Benjamin’s philosophy of history welcomes baudelairian poetic gestures.